2017
DOI: 10.1007/s11695-017-2857-5
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Treatment with Botulinum Toxin-A Is Not Effective: a Systematic Review and Meta-Analysis

Abstract: The effectiveness of gastric injections of botulinum toxin-A (BTA) as primary treatment for obesity is not well known since results in literature are discrepant. Hence, we aimed to systematically review and meta-analyze the available data to assess the real effect of BTA therapy. We searched MEDLINE, Embase, Cochrane, SCOPUS, EBSCO, LILACS, and BVS. We considered eligible only randomized controlled trials enrolling obese patients comparing BTA versus saline injections. Our initial search identified 8811 record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…The neuromuscular blockade caused by BTX-A provokes the thesis that this agent can be applied to the gastric wall, resulting in the feeling of bloating, delayed gastric emptying, early satiety, and weight loss. The main advantage of using the intragastric injection of BTX-A would be the absence of serious adverse events related to the procedure [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neuromuscular blockade caused by BTX-A provokes the thesis that this agent can be applied to the gastric wall, resulting in the feeling of bloating, delayed gastric emptying, early satiety, and weight loss. The main advantage of using the intragastric injection of BTX-A would be the absence of serious adverse events related to the procedure [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are studies showing that intragastric Botox treatment is ineffective in weight loss. Bustamante et al designed a meta-analysis with four randomized clinical trials [ 12 ]. They concluded that homogeneous randomized controlled studies did not find superiority of BTX-A versus placebo [ 6 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…[93][94][95] Botulinum toxin A (BTA) (not FDA approved) injection has been used in BE because of its effect on blocking the acetylcholine release that induces a transitory delay of the gastric emptying and reduction in maximal gastric capacity. 96,97 A systematic review by Bustamante and colleagues 98 stated against the use of BTA as not effective in achieving a significant TBWL greater than placebo. These results were confirmed in a very recent randomized clinical trial.…”
Section: Gastroduodenojejunal Bypass Sleeve (Gjbs)mentioning
confidence: 99%
“…[ 46 ] More recently, however, a systematic review and meta-analysis of BTA injection concluded that treatment of obesity with BTA is not effective. [ 47 ]…”
Section: E Ndoscopic M Ethodsmentioning
confidence: 99%